Educational foundations in the implementation of the merdeka curriculum: A philosophical, sociological, and psychological review - Nurhadi, Ahmad; Salim, Asep Agus; Ferawati, Desi; Sadiyah, Elim Halimah; Nurasiah, Noni; Maifi, Rista; Sariwardani, RR. Andriani (Institute of Computer Science (IOCS), 2026)
Background: The implementation of the Merdeka Curriculum requires a strong conceptual understanding to ensure that curriculum reform goes beyond administrative changes and reflects meaningful educational goals. Educational foundations play a crucial role in guiding curriculum policy formulation and implementation. Purpose: This article aims to analyze the role of philosophical, sociological, and psychological educational foundations in the implementation of the Merdeka Curriculum. Method: This study employed a qualitative approach using a literature review method. Data were collected from books, reputable national and international journal articles, and relevant educational policy documents. The data were analyzed thematically to identify the interconnections among educational foundations. Results: The findings indicate that philosophical foundations provide value orientation and educational goals through an emphasis on student-centered learning and character development. Sociological foundations ensure curriculum relevance to social, cultural, and community needs through flexibility and contextual learning. Psychological foundations support learning practices that consider students’ development, interests, and individual differences through differentiated instruction and formative assessment. Conclusion: The integration of philosophical, sociological, and psychological foundations is a critical prerequisite for ensuring that the Merdeka Curriculum is implemented consistently, contextually, and meaningfully, thereby supporting student-centered learning.